A coalitional game theoretic energy transaction algorithm for networked microgrids. (January 2023) - Sun, Rui; Wang, Luhao; Song, Wen; Li, Guanguan; Li, Qiqiang
Abstract: With the large-scale application of microgrid technology in distribution networks, emerging energy transactions among multiple microgrids as well as between microgrids and the grid increase the operational burden to the power system. To coordinate these energy transactions, a coalitional game theoretic energy transaction algorithm for networked microgrids is developed in this paper to improve energy exchange efficiency. First, a distance-oriented method for maximizing coalition utilities is proposed to guide the order of transactions in a coalition, and the corresponding coalition utility would be fairly allocated by the Shapley value. Second, a modified coalition formation algorithm consisting of perturbation, merge and split procedures is designed to obtain a D c -stable otherwise a better D h p -stable partition on the network, in which no microgrid has an incentive to leave this partition, and the corresponding theoretical proof is given in this paper. Finally, relative to the non-cooperation mode and the Merge&Split procedure, simulation results show the advantages of the proposed algorithm in reducing costs and facilitating energy transactions in the network. Highlights: Solved the cooperative energy transaction problem for networked microgrids in the network. A distance-oriented method is proposed to calculate the total utility for every valid microgrid coalition. A perturbation procedure is introduced to obtain a D c -stable otherwise a better D h p -stable partition. A theoretical proof for stability and optimality of the obtained coalition partition.